Resíduos sólidos no Brasil: contexto, lacunas e tendência - Deus, Rafael Mattos; Battistelle, Rosane Aparecida Gomes [UNESP]; Silva, Gustavo Henrique Ribeiro [UNESP] (FapUNIFESP (SciELO), 2015)
The theme of solid waste is in high evidence today, a fact noted by the recent implementation of the European directive, and in Brazil, by the National Solid Waste Policy. Understanding the impact of this policy on the national scientific production is essential to plan new directions and research trends. Through a bibliometric and scientometric studied, this research analyzed the national and global context of the last 20 years and found areas in which research progressed, as municipal solid waste, and essentials gaps to develop more the national state-of-the-art, as solid waste of transport. So, the results of this study are a plausible tool to justify for further research on this topic.

O tema resíduos sólidos está em evidência na sociedade moderna, fato observado pela recente implantação da diretiva europeia, e no Brasil, com a criação da Política Nacional de Resíduos Sólidos. Entender o impacto dessa política na produção científica nacional é essencial para traçar novos rumos e tendências de pesquisa. Por meio de um estudo bibliométrico e cientométrico, esta pesquisa traçou o contexto nacional e global dos últimos 20 anos e encontrou áreas em que as pesquisas avançaram, como em resíduos sólidos urbanos, e lacunas essenciais para desenvolver mais o estado-da-arte nacional, como resíduos sólidos do transporte. Assim, os resultados encontrados fazem deste estudo uma ferramenta plausível como justificativa para novas pesquisas no tema.
Solid waste in Brazil: context, gaps and trends
Keywords: Solid waste; Bibliometrics; Scientometrics; Sustainability; Trends; Resíduos sólidos; Bibliometria; Cientometria; Sustentabilidade; Tendências